Whole-Genome Sequencing Snapshot of Clinically Relevant Carbapenem-Resistant Gram-Negative Bacteria from Wastewater in Serbia - Ivana Cirkovic; Bruno H. Muller; Ana Janjusevic; Patrick Mollon; Valérie Istier; Caroline Mirande-Meunier; Snezana Brkic (Antibiotics, 2023)
Wastewater (WW) is considered a source of antibiotic-resistant bacteria with clinical relevance and may, thus, be important for their dissemination into the environment, especially in countries with poor WW treatment. To obtain an overview of the occurrence and characteristics of carbapenem-resistant Gram-negative bacteria (CR-GNB) in WW of Belgrade, we investigated samples from the four main sewer outlets prior to effluent into international rivers, the Sava and the Danube. Thirty-four CR-GNB isolates were selected for antimicrobial susceptibility testing (AST) and whole-genome sequencing (WGS). AST revealed that all isolates were multidrug-resistant. WGS showed that they belonged to eight different species and 25 different sequence types (STs), seven of which were new. ST101 K. pneumoniae (blaCTX-M-15/blaOXA-48) with novel plasmid p101_srb was the most frequent isolate, detected at nearly all the sampling sites. The most frequent resistance genes to aminoglycosides, quinolones, trimethroprim-sulfamethoxazole, tetracycline and fosfomycin were aac(6′)-Ib-cr (55.9%), oqxA (32.3%), dfrA14 (47.1%), sul1 (52.9%), tet(A) (23.5%) and fosA (50%), respectively. Acquired resistance to colistin via chromosomal-mediated mechanisms was detected in K. pneumoniae (mutations in mgrB and basRS) and P. aeruginosa (mutation in basRS), while a plasmid-mediated mechanism was confirmed in the E. cloacae complex (mcr-9.1 gene). The highest number of virulence genes (>300) was recorded in P. aeruginosa isolates. Further research is needed to systematically track the occurrence and distribution of these bacteria so as to mitigate their threat.